2019
DOI: 10.24167/psidim.v18i2.2305
|View full text |Cite
|
Sign up to set email alerts
|

Peterpan Syndrome Phenomenon : Self-Identity Crisis In Forming Intimation In Adult Man

Abstract: Peter Pan syndrome is inspired by the popular story of a child who has never grown up from a dream land. The term Peter Pan syndrome is given to men who enter adulthood but behave childish characterized by behavior that refuses social responsibility and difficulty forming commitment in interpersonal relationships. Individuals with Peter Pan syndrome are shown as someone loves fun, brave, likes challenges and has a great view of themselves. On the other hand, individual Peter Pan syndrome has a excessive anxiet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The more significant distinguishability between social and personal identity, the more barriers will be triggered, whilst the separation phase was separately signed by personal relationships or partnerships in the classes. This situation seemed to be a vacuum identity as caused by her uncertainty inner and outer roles since the only motive dealt with running away from the problems (Arini, 2019). Further, Ocha's learning disabilities needed extra time to reply to responses or answers, since they arranged a temporary moment in their silence to manage their thoughts without providing them glimmers (Otanjac, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The more significant distinguishability between social and personal identity, the more barriers will be triggered, whilst the separation phase was separately signed by personal relationships or partnerships in the classes. This situation seemed to be a vacuum identity as caused by her uncertainty inner and outer roles since the only motive dealt with running away from the problems (Arini, 2019). Further, Ocha's learning disabilities needed extra time to reply to responses or answers, since they arranged a temporary moment in their silence to manage their thoughts without providing them glimmers (Otanjac, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies reported students' learning disabilities regarding the influence of its affective factors on their learning performances. Arini (2019) firstly turned out that the Cinderella complex relied on woman's behaviours refusing social responsibilities and commitment in interpersonal relationships, where this complex happened during her early adulthoods conforming all about self-responsibilities. The complex was remarkably documented that its symptom was due to central nervous system dysfunction that possibly occurred across the women's life span, whilst self-regulatory behaviours, self-esteem, social perception, interaction (Illinois Community College Board, 2014), and direct and indirect relationships intrinsically (Sanford, 2015) became the contributing factors towards this complex.…”
Section: Introductionmentioning
confidence: 99%
“…The concept of people who do not want to grow up was called Peter Pan Syndrome. There have a large number of researchers has studied this subject, including Peter Pan Syndrome in marriage (5); man's Peter Pan Syndrome with adolescent mothers' intimate relationships (6); Peter Pan Syndrome among mountain climbers (7); Peter Pan Syndrome in churches (8); the phenomenon of Peter Pan Syndrome in adult man (9); Peter Pan Syndrome among anorexia nervosa patients (10).…”
Section: Introductionmentioning
confidence: 99%
“…The study of Kiley (11) has suggested that the concept "Peter Pan Syndrome" has recently gained popularity as a metaphor for "men who have never grown up". Some previous studies revealed the manifestation of a person who has Peter Pan Syndrome that person who refuse to comply with the characteristics of the adult when reaching adulthood Kiley (11); they are unable to cope with adult emotions and responsibilities, difficulty in social and professional relationships and behave childish characterized (9,12); staying a child and sustaining the parents' protection (13), postponing between childhood and adulthood (10). Quadrio (1982) described the concept "Peter Pan Syndrome" as a man married who is immature, narcissistic, and unfaithful.…”
Section: Introductionmentioning
confidence: 99%